Modified ethylene-vinyl alcohol copolymer
The modified ethylene-vinyl alcohol copolymer addresses the challenge of reduced barrier properties and adhesion under high humidity by optimizing monomer content and saponification, ensuring effective gas barrier performance and improved processability.
Patent Information
- Application Number
- JP2021128427
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-04
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2041-08-04
AI Technical Summary
Existing ethylene-vinyl alcohol copolymers suffer from reduced gas barrier properties under high humidity conditions and poor interlayer adhesion, leading to issues like delamination and environmental concerns due to fluorine-containing groups.
A modified ethylene-vinyl alcohol copolymer with specific monomer content ratios and high saponification degree, incorporating monomer units with hydroxyl groups or ester bonds, enhances gas barrier properties and interlayer adhesion while minimizing environmental impact.
The modified copolymer maintains excellent gas barrier properties at high humidity and improves secondary processability, with enhanced interlayer adhesion and reduced disposal issues, suitable for various packaging applications.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a modified ethylene-vinyl alcohol copolymer and a method for producing the same. [Background technology]
[0002] Ethylene-vinyl alcohol copolymer (hereinafter sometimes abbreviated as EVOH) is a thermoplastic resin with excellent gas barrier properties, and taking advantage of this gas barrier property, it is widely used as various packaging materials such as films, sheets, containers, etc. However, since the gas barrier property is significantly reduced under high humidity conditions, there was a problem that the gas barrier property was insufficient when the package was stored in a high humidity environment.
[0003] In response to this, a method for improving the gas barrier property of EVOH under high humidity has been proposed. For example, Patent Document 1 describes a gas barrier material made of an EVOH copolymer having a fluorine-containing group, which is said to improve the gas barrier property under high humidity. However, since the gas barrier material contains a persistent fluorine-containing group, it may affect the ecosystem for a long period of time if it is discharged into the environment. In addition, a multilayer structure containing the EVOH copolymer having a fluorine-containing group has low interlayer adhesion and may cause problems such as delamination during use.
[0004] In addition, Patent Document 2 reports that a modified ethylene-vinyl alcohol copolymer containing a monomer unit containing a plurality of hydroxyl groups or ester bonds has excellent secondary processability, but its barrier properties under high humidity conditions cannot be said to be superior to those of an unmodified ethylene-vinyl alcohol copolymer. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-282835 A [Patent Document 2] JP 2014-051647 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a novel ethylene-vinyl alcohol copolymer which has excellent gas barrier properties at high humidity, excellent secondary processability and interlayer adhesion, and which causes few problems in terms of disposal. [Means for solving the problem]
[0007] The above-mentioned problem can be solved by providing a modified ethylene-vinyl alcohol copolymer represented by the following formula (I), in which the contents (mol %) of a, b and c relative to all monomer units satisfy the following formulas (1) to (3), and the degree of saponification (DS) defined by the following formula (4) is 90 mol % or more.
[0008] [ka]
[0009] [In formula (I), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, which may contain a hydroxyl group or an alkoxy group. A represents an alkylene group having 0 to 10 carbon atoms, which may contain a hydroxyl group or an alkoxy group. When A is an alkylene group having 0 carbon atoms, this means that the carbon atom bonded to A and the oxygen atom are directly bonded without any other atom being interposed therebetween. B represents an alkylene group having 1 to 10 carbon atoms, which may contain a hydroxyl group or an alkoxy group. X, Y, and Z each independently represent a hydrogen atom, a formyl group, or an alkanoyl group having 2 to 10 carbon atoms. 18≦a≦55 (1) 0.01≦c≦20 (2) [100-(a+c)]×0.9≦b≦[100-(a+c)] (3) DS = [(total number of moles of X, Y, and Z that are hydrogen atoms) / (total number of moles of X, Y, and Z)] × 100 (4)
[0010] At this time, R 1 , R 2 , R 3 and R 4 is preferably a hydrogen atom. It is also preferable that A and B are each independently a methylene group. It is also preferable that X, Y and Z are each independently a hydrogen atom or an acetyl group. It is also preferable that the oxygen transmission rate at 20°C and 85% RH is 100cc 20μm / m2 day atm or less.
[0011] A barrier material containing the modified ethylene-vinyl alcohol copolymer is a preferred embodiment. A resin composition containing the modified ethylene-vinyl alcohol copolymer is also a preferred embodiment, and the resin composition preferably contains the modified ethylene-vinyl alcohol copolymer and an alkali metal salt, and the alkali metal salt is preferably contained in an amount of 10 to 500 ppm in terms of the alkali metal element.
[0012] A multilayer structure including a layer of the modified ethylene-vinyl alcohol copolymer and a layer of another thermoplastic resin is also a preferred embodiment. In this case, it is preferred that the layer of the modified ethylene-vinyl alcohol copolymer and the layer of another thermoplastic resin are bonded via a layer of an adhesive resin. In this case, it is also preferred that the adhesive resin is a polyolefin having a carboxyl group, a carboxylic anhydride group, or an epoxy group. Effect of the Invention
[0013] The modified ethylene-vinyl alcohol copolymer of the present invention has excellent gas barrier properties at high humidity, and is also excellent in secondary processability and interlayer adhesion, and can be suitably used as a barrier material with few disposal problems. It can also be molded into various shapes such as films, cups, bottles, etc., and can be suitably used as various containers and multilayer structures. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] The modified ethylene-vinyl alcohol copolymer of the present invention is a modified ethylene-vinyl alcohol copolymer represented by formula (I), in which the contents (mol%) of a, b, and c relative to the total monomer units satisfy the following formulas (1) to (3), and the degree of saponification (DS) defined by the following formula (4) is 90 mol% or more. This modified ethylene-vinyl alcohol copolymer has a monomer unit having 5 or more carbon atoms in addition to an ethylene unit and a vinyl alcohol unit, and therefore the crystallinity is reduced compared to an ethylene-vinyl alcohol copolymer that does not contain the monomer unit, and flexibility and secondary processability can be improved. In addition, this modified ethylene-vinyl alcohol copolymer can reduce the decrease in barrier property caused by the decrease in crystallinity due to the strong hydrogen bonding force of multiple hydroxyl groups in the side chains of the monomer units including Y and Z shown at the right end in formula (I). In other words, flexibility and secondary processability can be improved while minimizing the decrease in barrier performance.
[0015] In formula (I), R 1 , R 2 , R 3 and R 4 each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms, which may contain a hydroxyl group, an alkoxy group, or a halogen atom. X, Y, and Z each independently represent a hydrogen atom, a formyl group, or an alkanoyl group having 2 to 10 carbon atoms.
[0016] In formula (I), R 1 , R 2 , R 3 and R 4 R each independently represents a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. 1 , R 2 , R 3 and R 4 may be the same or different. The structure of the alkyl group is not particularly limited, and may partially have a branched structure or a cyclic structure. The alkyl group may contain a hydroxyl group, an alkoxy group, or a halogen atom. R 1 , R2 , R 3 and R 4 is preferably a hydrogen atom or an alkyl group having 1 to 5 carbon atoms, more preferably a hydrogen atom. Suitable examples of the alkyl group include linear or branched alkyl groups such as a methyl group, an ethyl group, an n-propyl group, an isopropyl group, an n-butyl group, an isobutyl group, a tert-butyl group, and a pentyl group.
[0017] In formula (I), X, Y and Z each independently represent a hydrogen atom, a formyl group or an alkanoyl group having 2 to 10 carbon atoms. When X, Y or Z is a hydrogen atom, formula (I) has a hydroxyl group, and when X, Y or Z is a formyl group or an alkanoyl group, formula (I) has an ester group. The alkanoyl group is preferably an alkanoyl group having 2 to 5 carbon atoms, and suitable examples include an acetyl group, a propanoyl group and a butanoyl group. Among these, an acetyl group is particularly suitable. It is preferable that X, Y and Z are all hydrogen atoms or a mixture containing hydrogen atoms.
[0018] The monomer unit containing X is usually obtained by saponifying a vinyl ester. Therefore, it is preferable that X is a mixture of a hydrogen atom and a formyl group or an alkanoyl group having 2 to 10 carbon atoms. Considering the availability of the monomer (vinyl acetate) and the production cost, it is particularly preferable that X is a mixture of a hydrogen atom and an acetyl group.
[0019] On the other hand, the monomer unit containing Y and Z can be produced by copolymerizing an unsaturated monomer unit having a diester structure and then saponifying it, or by copolymerizing an unsaturated monomer unit having a diol structure as it is. Therefore, Y and Z may each be a hydrogen atom only, or a mixture of a hydrogen atom and a formyl group or an alkanoyl group having 2 to 10 carbon atoms, or more preferably a mixture of a hydrogen atom and an acetyl group.
[0020] In the modified ethylene-vinyl alcohol copolymer of the present invention, the contents (mol %) of a, b and c relative to the total monomer units satisfy the following formulae (1) to (3). 18≦a≦55 (1) 0.01≦c≦20 (2) [100-(a+c)]×0.9≦b≦[100-(a+c)] (3)
[0021] a indicates the content (mol %) of ethylene units relative to all monomer units, and is 18 to 55 mol %. If the ethylene unit content is less than 18 mol %, the melt moldability of the modified ethylene-vinyl alcohol copolymer deteriorates. a is preferably 22 mol % or more. On the other hand, if the ethylene unit content exceeds 55 mol %, the barrier property of the modified ethylene-vinyl alcohol copolymer becomes insufficient. a is preferably 50 mol % or less.
[0022] c indicates the content (mol%) of the monomer units including Y and Z shown at the right end in formula (I) relative to the total monomer units, and is 0.01 to 20 mol%. If c is less than 0.01 mol%, the secondary processability of the modified ethylene-vinyl alcohol copolymer becomes insufficient. c is preferably 0.1 mol% or more, and more preferably 0.5 mol% or more. On the other hand, if c exceeds 20 mol%, the crystallinity is extremely reduced, and the barrier property of the modified ethylene-vinyl alcohol copolymer is reduced. c is preferably 10 mol% or less, and more preferably 5 mol% or less.
[0023] b indicates the content (mol %) of vinyl alcohol units and vinyl ester units relative to the total monomer units, which satisfies the following formula (3). [100-(a+c)]×0.9≦b≦[100-(a+c)] (3) That is, in the modified ethylene-vinyl alcohol copolymer of the present invention, 90% or more of the monomer units other than ethylene units and the monomer units containing Y and Z shown at the right end in formula (I) are vinyl alcohol units or vinyl ester units. If formula (3) is not satisfied, the gas barrier property will be insufficient. Preferably, the following formula (3') is satisfied, and more preferably, the following formula (3") is satisfied. [100-(a+c)]×0.95≦b≦[100-(a+c)] (3') [100-(a+c)]×0.98≦b≦[100-(a+c)] (3”)
[0024] The modified ethylene-vinyl alcohol copolymer of the present invention has a degree of saponification (DS) defined by the following formula (4) of 90 mol % or more. DS = [(total number of moles of X, Y, and Z that are hydrogen atoms) / (total number of moles of X, Y, and Z)] × 100 (4) Here, "the total number of moles of hydrogen atoms among X, Y and Z" refers to the number of moles of hydroxyl groups, and "the total number of moles of X, Y and Z" refers to the total number of moles of hydroxyl groups and ester groups. If the saponification degree (DS) is less than 90 mol%, not only will sufficient barrier performance not be obtained, but the thermal stability will be insufficient, and gels and bumps will be easily generated during melt molding. The saponification degree (DS) is preferably 95 mol% or more, more preferably 98 mol% or more, and even more preferably 99 mol% or more.
[0025] The degree of saponification (DS) can be obtained by the nuclear magnetic resonance (NMR) method. The contents of the monomer units represented by a, b, and c above can also be obtained by the NMR method. The modified ethylene-vinyl alcohol copolymer of the present invention is usually a random copolymer. It can be confirmed that it is a random copolymer by the measurement results of NMR or melting point.
[0026] The melt flow rate (MFR) (190°C, under a load of 2160g) of the modified ethylene-vinyl alcohol copolymer of the present invention is preferably 0.1 to 30g / 10min, more preferably 0.3 to 25g / 10min, and even more preferably 0.5 to 20g / 10min. However, for those having a melting point near or exceeding 190°C, the MFR is measured under a load of 2160g at multiple temperatures equal to or higher than the melting point, and is plotted on a semi-logarithmic graph with the reciprocal of absolute temperature on the horizontal axis and the logarithm of MFR on the vertical axis, and is expressed as a value extrapolated to 190°C.
[0027] Here, when the modified ethylene-vinyl alcohol copolymer is a mixture of two or more different types of modified ethylene-vinyl alcohol copolymers, the content, degree of saponification and MFR of the monomer units represented by a, b and c are average values calculated from the blending weight ratio.
[0028] The oxygen transmission rate of the modified ethylene-vinyl alcohol copolymer of the present invention at 20°C and 85% RH is preferably 100 cc 20 μm / m2 day atm or less, more preferably 10 cc 20 μm / m2 day atm or less, and even more preferably 5 cc 20 μm / m2 day atm or less.
[0029] The method for producing the modified ethylene-vinyl alcohol copolymer of the present invention is not particularly limited. For example, a method in which ethylene, a vinyl ester represented by the following formula (II), and an unsaturated monomer represented by the following formula (III) are radically polymerized to obtain a modified ethylene-vinyl ester copolymer represented by the following formula (IV), and then the copolymer is saponified can be mentioned.
[0030] [ka]
[0031] In formula (II), R 5represents a hydrogen atom or an alkyl group having 1 to 9 carbon atoms. The number of carbon atoms in the alkyl group is preferably 1 to 4. Examples of the vinyl ester represented by formula (II) include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, and vinyl caproate. From an economical viewpoint, vinyl acetate is particularly preferred.
[0032] [ka]
[0033] In formula (III), R 1 , R 2 , R 3 and R 4 is the same as in formula (I). 6 and R 7 each independently represents a hydrogen atom or an alkyl group having 1 to 9 carbon atoms. The number of carbon atoms in the alkyl group is preferably 1 to 4. A represents an alkylene group having 0 to 10 carbon atoms, which may contain a hydroxyl group or an alkoxy group. When A is an alkylene group having 0 carbon atoms, it means that the carbon atom bonded to A and the oxygen atom are directly bonded without any other atom being interposed therebetween. B represents an alkylene group having 1 to 10 carbon atoms, which may contain a hydroxyl group or an alkoxy group. Examples of the unsaturated monomer represented by formula (III) include 1,5-diacetoxy-3-methylenepentane, 1,4-diacetoxy-2-methylenebutane, 1,5-diacetoxy-2,4-methyl-3-methylenepentane, 1,6-diacetoxy-3-methylenehexane, and 1,7-diacetoxy-4-methyleneheptane. Among these, 1,5-diacetoxy-3-methylenepentane is preferably used because it is easy to produce. In the case of 1,5-diacetoxy-3-methylenepentane, R 1 , R 2 , R 3 and R 4 is a hydrogen atom, R6 and R7 are methyl groups, and A and B are methylene groups.
[0034] [ka]
[0035] In formula (IV), R 1 , R 2 , R 3 , R 4 , R 5 , R 6 , R 7 , a, b and c are the same as those in the formulae (I) to (III). The modified ethylene-vinyl ester copolymer thus obtained is a novel polymer, and is then subjected to a saponification treatment.
[0036] Alternatively, instead of the unsaturated monomer represented by formula (III) above, the unsaturated monomer represented by formula (V) below may be copolymerized. In this case, only the units derived from the unsaturated monomer represented by formula (II) above are saponified by the saponification treatment.
[0037] [ka]
[0038] In formula (V), R 1 , R 2 , R 3 and R 4 The formula (V) is the same as that of the formula (I). The unsaturated monomer represented by the formula (V) includes 3-methylene-1,5-pentanediol.
[0039] The unsaturated monomers represented by formula (III) and formula (V) used in the present invention have high copolymerization reactivity with vinyl ester monomers, so that the copolymerization reaction proceeds easily. Therefore, it is easy to increase the modification amount and polymerization degree of the resulting modified ethylene-vinyl ester copolymer. In addition, even if the polymerization reaction is stopped at a low polymerization rate, the amount of unreacted unsaturated monomer remaining at the end of the polymerization is small, so it is also excellent in terms of environment and cost. In this respect, the unsaturated monomers represented by formula (III) and formula (V) are superior to other monomers having only one carbon atom with a functional group at the allyl position, such as allyl glycidyl ether and 3,4-diacetoxy-1-butene. Here, the unsaturated monomer represented by formula (III) is more reactive than the unsaturated monomer represented by formula (V).
[0040] The polymerization method for producing a modified ethylene-vinyl ester copolymer by copolymerizing ethylene, a vinyl ester represented by the above formula (II), and an unsaturated monomer represented by the above formula (III) or (V) may be any of batch polymerization, semi-batch polymerization, continuous polymerization, and semi-continuous polymerization. In addition, known methods such as bulk polymerization, solution polymerization, suspension polymerization, and emulsion polymerization can be adopted as the polymerization method. Bulk polymerization or solution polymerization, in which polymerization is carried out without a solvent or in a solvent such as alcohol, is usually adopted. When a modified ethylene-vinyl ester copolymer with a high degree of polymerization is to be obtained, the adoption of an emulsion polymerization method is one of the options.
[0041] The solvent used in the solution polymerization method is not particularly limited, but alcohol is preferably used, and for example, lower alcohols such as methanol, ethanol, propanol, etc. The amount of the solvent used in the polymerization reaction solution may be selected in consideration of the viscosity average polymerization degree of the target modified ethylene-vinyl alcohol copolymer and chain transfer of the solvent, and the weight ratio of the solvent to the total monomers contained in the reaction solution (solvent / total monomers) is selected in the range of 0.01 to 10, preferably 0.05 to 3.
[0042] The polymerization initiator used in copolymerizing ethylene, the vinyl ester represented by the above formula (II), and the unsaturated monomer represented by the above formula (III) or (V) is selected from known polymerization initiators, such as azo initiators, peroxide initiators, and redox initiators, depending on the polymerization method. Examples of the azo initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethylvaleronitrile), and 2,2'-azobis(4-methoxy-2,4-dimethylvaleronitrile). Examples of peroxide initiators include percarbonate compounds such as diisopropyl peroxydicarbonate, di-2-ethylhexyl peroxydicarbonate, and diethoxyethyl peroxydicarbonate; perester compounds such as t-butyl peroxyneodecanate, α-cumyl peroxyneodecanate, and acetyl peroxide; acetylcyclohexylsulfonyl peroxide; and 2,4,4-trimethylpentyl-2-peroxyphenoxyacetate. Potassium persulfate, ammonium persulfate, and hydrogen peroxide may be used in combination with the above initiators. Redox initiators are polymerization initiators that combine the above peroxide initiators with reducing agents such as sodium hydrogen sulfite, sodium hydrogen carbonate, tartaric acid, L-ascorbic acid, and Rongalite. The amount of polymerization initiator used cannot be determined in general because it varies depending on the polymerization catalyst, but is adjusted according to the polymerization rate. The amount of the polymerization initiator used is preferably 0.01 to 0.2 mol %, more preferably 0.02 to 0.15 mol %, based on the vinyl ester monomer. The polymerization temperature is not particularly limited, but is suitably from room temperature to about 150° C., and is preferably 40° C. or higher and not higher than the boiling point of the solvent used.
[0043] When copolymerizing ethylene, a vinyl ester represented by the above formula (II), and an unsaturated monomer represented by the above formula (III) or (V), the copolymerization may be carried out in the presence of a chain transfer agent, provided that the effects of the present invention are not impaired. Examples of the chain transfer agent include aldehydes such as acetaldehyde and propionaldehyde; ketones such as acetone and methyl ethyl ketone; mercaptans such as 2-hydroxyethanethiol; and phosphinates such as sodium phosphinate monohydrate. Among these, aldehydes and ketones are preferably used. The amount of the chain transfer agent added to the polymerization reaction solution is determined according to the chain transfer coefficient of the chain transfer agent and the polymerization degree of the desired modified ethylene-vinyl ester copolymer, and is generally preferably 0.1 to 10 parts by mass relative to 100 parts by mass of the vinyl ester monomer.
[0044] The modified ethylene-vinyl ester copolymer thus obtained can be saponified to obtain the modified ethylene-vinyl alcohol copolymer of the present invention. At this time, the vinyl ester units in the copolymer are converted to vinyl alcohol units. At the same time, the ester bonds derived from the unsaturated monomer represented by formula (III) are also hydrolyzed and converted to 1,5-diol structures. In this way, different types of ester groups can be hydrolyzed simultaneously by a single saponification reaction.
[0045] A known method can be adopted as a method for saponifying the modified ethylene-vinyl ester copolymer. The saponification reaction is usually carried out in a solution of alcohol or water-containing alcohol. The alcohol preferably used at this time is a lower alcohol such as methanol or ethanol, and particularly preferably methanol. The alcohol or water-containing alcohol used in the saponification reaction may contain other solvents such as acetone, methyl acetate, ethyl acetate, benzene, etc., so long as the amount of the other solvents is 40% by weight or less. The catalyst used in the saponification is, for example, an alkali metal hydroxide such as potassium hydroxide or sodium hydroxide, an alkali catalyst such as sodium methylate, or an acid catalyst such as a mineral acid. The temperature at which the saponification is carried out is not limited, but is preferably in the range of 20 to 120°C. When a gel-like product precipitates as the saponification proceeds, the product can be crushed, washed, and dried to obtain a modified ethylene-vinyl alcohol copolymer.
[0046] The modified ethylene-vinyl alcohol polymer of the present invention may contain structural units derived from other ethylenically unsaturated monomers copolymerizable with ethylene, the vinyl ester represented by the above formula (II), and the unsaturated monomer represented by the above formula (III) or (V), as long as the effects of the present invention are not impaired. Examples of such ethylenically unsaturated monomers include α-olefins such as propylene, n-butene, isobutylene, and 1-hexene; acrylic acid and its salts; unsaturated monomers having an acrylic acid ester group; methacrylic acid and its salts; unsaturated monomers having a methacrylic acid ester group; acrylamide, N-methylacrylamide, N-ethylacrylamide, N,N-dimethylacrylamide, diacetoneacrylamide, acrylamidopropanesulfonic acid and its salts, acrylamidopropyldimethylamine and its salts (e.g., quaternary salts); methacrylamide, N-methylmethacrylamide, N-ethylmethacrylamide, methacrylamidopropanesulfonic acid and its salts, methacrylamidopropyldimethylamine and its salts (e.g., quaternary salts); methyl vinyl ether, ethylenediamine ... vinyl ethers such as ethyl vinyl ether, n-propyl vinyl ether, i-propyl vinyl ether, n-butyl vinyl ether, i-butyl vinyl ether, t-butyl vinyl ether, dodecyl vinyl ether, stearyl vinyl ether, 2,3-diacetoxy-1-vinyloxypropane; vinyl cyanides such as acrylonitrile and methacrylonitrile; vinyl halides such as vinyl chloride and vinyl fluoride; vinylidene halides such as vinylidene chloride and vinylidene fluoride; allyl compounds such as allyl acetate, 2,3-diacetoxy-1-allyloxypropane, and allyl chloride; unsaturated dicarboxylic acids and salts or esters thereof such as maleic acid, itaconic acid, and fumaric acid; vinyl silane compounds such as vinyltrimethoxysilane; and isopropenyl acetate.
[0047] The modified ethylene-vinyl alcohol copolymer of the present invention thus obtained can be blended with other components to form a resin composition, for example, other thermoplastic resins, plasticizers, lubricants, stabilizers, surfactants, colorants, ultraviolet absorbers, antistatic agents, drying agents, crosslinking agents, metal salts, fillers, reinforcing agents such as various fibers, and the like.
[0048] In particular, the modified ethylene-vinyl alcohol copolymer of the present invention preferably contains an alkali metal salt. By forming a resin composition containing an alkali metal salt in this way, the interlayer adhesion when laminated with other resins is improved. The cation species of the alkali metal salt is not particularly limited, but sodium salt or potassium salt is preferable. The anion species of the alkali metal salt is also not particularly limited. It can be added as a carboxylate, carbonate, hydrogen carbonate, phosphate, hydrogen phosphate, borate, hydroxide, etc. The content of the alkali metal salt is preferably 10 to 500 ppm in terms of the alkali metal element. If the content of the alkali metal salt is less than 10 ppm, the interlayer adhesion may be insufficient, and more preferably 50 ppm or more. On the other hand, if the content of the alkali metal salt is more than 500 ppm, the melt stability may be insufficient, and more preferably 300 ppm or less.
[0049] It is also preferable that the modified ethylene-vinyl alcohol copolymer of the present invention contains a phosphoric acid compound. By forming a resin composition containing a phosphoric acid compound in this way, coloring during melt molding can be prevented. The phosphoric acid compound used in the present invention is not particularly limited, and various acids such as phosphoric acid and phosphorous acid and their salts can be used. The phosphate may be contained in the form of any of primary phosphate, secondary phosphate, and tertiary phosphate, but primary phosphate is preferred. The cationic species is also not particularly limited, but alkali metal salts are preferred. Among these, sodium dihydrogen phosphate and potassium dihydrogen phosphate are preferred. The content of the phosphoric acid compound is preferably 5 to 200 ppm in terms of phosphate radical. If the content of the phosphoric acid compound is less than 5 ppm, the coloring resistance during melt molding may be insufficient. On the other hand, if the content of the phosphoric acid compound exceeds 200 ppm, the melt stability may be insufficient, and it is more preferably 160 ppm or less.
[0050] The modified ethylene-vinyl alcohol copolymer of the present invention may contain a boron compound. By forming a resin composition containing a boron compound in this way, torque fluctuation during heat melting can be suppressed. The boron compound used in the present invention is not particularly limited, and examples thereof include boric acids, boric acid esters, borate salts, boron hydrides, and the like. Specifically, examples of boric acids include orthoboric acid, metaboric acid, tetraboric acid, and the like, examples of boric acid esters include triethyl borate, trimethyl borate, and the like, and examples of borates include alkali metal salts, alkaline earth metal salts, borax, and the like of the above-mentioned various boric acids. Among these compounds, orthoboric acid (hereinafter, sometimes simply referred to as boric acid) is preferred. The content of the boron compound is preferably 20 to 2000 ppm or less in terms of boron element. If the content of the boron compound is less than 20 ppm, the suppression of torque fluctuation during heat melting may be insufficient, and it is more preferably 50 ppm or more. On the other hand, if the content of the boron compound exceeds 2000 ppm, gelation may occur easily and moldability may deteriorate, and therefore the content is more preferably 1000 ppm or less.
[0051] In addition, to the extent that the effects of the present invention are not impaired, the resin composition may contain 0.001 to 1% by weight of one or more of hydrotalcite compounds, hindered phenol-based and hindered amine-based heat stabilizers, and metal salts of higher aliphatic carboxylic acids (e.g., calcium stearate, magnesium stearate, etc.) to improve melt stability, etc. Specific examples of other components include the following.
[0052] Antioxidants: 2,5-di-t-butyl-hydroquinone, 2,6-di-t-butyl-p-cresol, 4,4'-thiobis-(6-t-butylphenol), 2,2'-methylene-bis-(4-methyl-6-t-butylphenol), octadecyl-3-(3',5'-di-t-butyl-4'-hydroxyphenyl)propionate, 4,4'-thiobis-(6-t-butylphenol), etc.
[0053] Ultraviolet absorbers: ethylene-2-cyano-3',3'-diphenylacrylate, 2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3'-t-butyl-5'-methylphenyl)5-chlorobenzotriazole, 2-hydroxy-4-methoxybenzophenone, 2,2'-dihydroxy-4-methoxybenzophenone, etc.
[0054] Plasticizers: dimethyl phthalate, diethyl phthalate, dioctyl phthalate, wax, liquid paraffin, phosphate esters, etc.
[0055] Antistatic agents: pentaerythritol monostearate, sorbitan monopalmitate, sulfated polyolefins, polyethylene oxide, carbowax, etc.
[0056] Lubricants: ethylene bisstearamide, butyl stearate, etc.
[0057] Colorants: carbon black, phthalocyanine, quinacridone, indoline, azo pigments, red iron oxide, etc.
[0058] Fillers: fiberglass, ballastonite, calcium silicate, etc.
[0059] Typically, the resin composition contains 50% by weight or more of the modified ethylene-vinyl alcohol copolymer. From the viewpoint of barrier properties, the resin composition preferably contains 75% by weight or more of the modified ethylene-vinyl alcohol copolymer, more preferably 95% by weight or more, and even more preferably 98% by weight or more.
[0060] The method for producing the resin composition is not particularly limited. The modified ethylene-vinyl alcohol copolymer and other components are mixed by a known method to obtain the resin composition. The modified ethylene-vinyl alcohol copolymer is immersed in an aqueous solution in which other components are dissolved, and the modified ethylene-vinyl alcohol copolymer contains the other components to obtain the resin composition.
[0061] The method for molding the modified ethylene-vinyl alcohol copolymer of the present invention is not particularly limited. Although it can be molded using a solution of the modified ethylene-vinyl alcohol copolymer, melt molding is preferred. By melt molding, various molded products such as films, sheets, containers, pipes, fibers, etc. can be obtained. Among them, films and sheets require flexibility and are often stretched after melt molding, so they are suitable applications for using the modified ethylene-vinyl alcohol copolymer of the present invention. Examples of melt molding methods include extrusion molding, injection molding, inflation molding, press molding, and blow molding. Among them, an extrusion molded product containing the modified ethylene-vinyl alcohol copolymer is a preferred embodiment.
[0062] The molded article made of the modified ethylene-vinyl alcohol copolymer of the present invention is often used as a multilayer structure containing the modified EVOH layer and another thermoplastic resin layer. In particular, a configuration in which the modified EVOH layer is an intermediate layer and another thermoplastic resin is disposed as an outer layer on both sides thereof is preferable. It is also preferable that the modified EVOH layer and the other thermoplastic resin layer are bonded via an adhesive resin layer. The modified EVOH layer has a barrier property, and its thickness is usually 3 to 250 μm, preferably 10 to 100 μm. On the other hand, the thermoplastic resin used in the outer layer is not particularly limited, and is appropriately selected in consideration of the required performance such as moisture permeability, heat resistance, heat sealability, transparency, etc. and the application. The thickness of the entire multilayer structure is not particularly limited, but is usually 15 to 6000 μm. A laminated film or laminated sheet obtained by laminating a layer made of another thermoplastic resin on a film or sheet containing the modified ethylene-vinyl alcohol copolymer is a preferred embodiment of the present invention.
[0063] Examples of other thermoplastic resin layers to be laminated with the modified EVOH layer of the present invention include polyolefins such as polyethylene, polypropylene, ethylene-vinyl acetate copolymers, and ethylene-(meth)acrylic acid ester copolymers; polyamides; polyesters; polystyrene; polyvinyl chloride; acrylic resins; polyvinylidene chloride; polyacetals; and polycarbonates.
[0064] The multilayer structure can be obtained by various manufacturing methods, and coextrusion, dry lamination, sand lamination, extrusion lamination, coextrusion lamination, solution coating, etc. can be adopted. Among these, the coextrusion method is a method in which modified EVOH and other thermoplastic resins are simultaneously extruded from an extruder, laminated in a molten state, and discharged from a die outlet in the form of a multilayer film. When forming a film by the coextrusion method, a method in which a modified EVOH layer and another thermoplastic resin layer are laminated with an adhesive resin layer sandwiched therebetween is preferred. As the adhesive resin, it is preferred to use a polyolefin having a carboxyl group, a carboxylic anhydride group, or an epoxy group. Such an adhesive resin has excellent adhesion to a modified ethylene-vinyl alcohol copolymer and to other thermoplastic resins not containing a carboxyl group, a carboxylic anhydride group, or an epoxy group.
[0065] Examples of polyolefins containing carboxyl groups include polyolefins copolymerized with acrylic acid or methacrylic acid. In this case, all or part of the carboxyl groups contained in the polyolefin may be present in the form of a metal salt, as typified by ionomers. Examples of polyolefins having carboxylic anhydride groups include polyolefins graft-modified with maleic anhydride or itaconic acid. Examples of polyolefin resins containing epoxy groups include polyolefins copolymerized with glycidyl methacrylate. Among these polyolefins having carboxyl groups, carboxylic anhydrides, or epoxy groups, polyolefins modified with carboxylic anhydrides such as maleic anhydride, particularly polyethylene and polypropylene, are preferred in terms of excellent adhesiveness.
[0066] The melt-molded product thus obtained is preferably further subjected to secondary processing. The modified ethylene-vinyl alcohol copolymer of the present invention has excellent secondary processability. Examples of the secondary processing method include uniaxial stretching, biaxial stretching, stretch blow molding, thermoforming, rolling, and the like. In particular, a film or sheet stretched at a high ratio is a preferred embodiment of the present invention. Specifically, a film or sheet obtained by stretching is a particularly preferred embodiment, and the stretching ratio is preferably 7 times or more, more preferably 8 times or more, and more preferably 9 times or more in terms of area ratio. Prior to the secondary processing, crosslinking may be performed by irradiation with radiation or the like.
[0067] The molded article of the present invention thus obtained has excellent barrier properties, flexibility and secondary processability, and can be molded into various shapes such as films, cups, bottles, etc., and can be suitably used as various containers, etc.
[0068] Among them, a thermoformed product containing the modified ethylene-vinyl alcohol copolymer of the present invention is a preferred embodiment. Thermoforming in the present invention means that a film or sheet is heated to soften it and then molded into a mold shape. As a molding method, a method of molding into a mold shape using vacuum or compressed air and, if necessary, a plug in combination (straight method, drape method, air slip method, snapback method, plug assist method, etc.) and a press molding method are preferred. Various molding conditions such as molding temperature, degree of vacuum, compressed air pressure, or molding speed are appropriately set depending on the plug shape, mold shape, or properties of the raw material film or raw material sheet. The molding temperature when the multilayer film or multilayer sheet is thermoformed is not particularly limited and is appropriately adjusted depending on the configuration of the multilayer film or multilayer sheet. For example, the molding temperature is preferably 130 to 200°C. EXAMPLES
[0069] The present invention will now be described in more detail with reference to examples.
[0070] Example 1 (1) Synthesis of modified EVAc In a 50 L pressurized reactor equipped with a jacket, a stirrer, a nitrogen inlet, an ethylene inlet, and an initiator addition inlet, vinyl acetate (R 5 21.0 kg of 3-methylene-1,5-pentane diacetate (wherein R is a methyl group; hereinafter referred to as VAc), 6.3 kg of methanol (hereinafter referred to as MeOH), and 1 , R 2 , R 3 and R 4 A hydrogen atom, A and B methylene groups, and Y and Z acetyl groups (hereinafter referred to as MPEDAc) was charged at 1.85 kg, and the temperature was raised to 60°C, followed by nitrogen bubbling for 30 minutes to replace the atmosphere in the reaction vessel with nitrogen. Ethylene was then introduced so that the reaction vessel pressure (ethylene pressure) was 3.6 MPa. The temperature in the reaction vessel was adjusted to 60°C, and 10.7 g of 2,2'-azobis(2,4-dimethylvaleronitrile) ("V-65" manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was added as a methanol solution as an initiator to start polymerization. During polymerization, the ethylene pressure was maintained at 3.6 MPa and the polymerization temperature at 60°C. After 4 hours, the polymerization was stopped by cooling when the conversion rate of VAc reached 43%. The reaction vessel was opened to remove ethylene, and then nitrogen gas was bubbled in to completely remove ethylene. Next, unreacted VAc was removed under reduced pressure, and then MeOH was added to a modified ethylene-vinyl acetate copolymer (sometimes referred to as modified EVAc in this specification) in which structural units derived from MPEDAc had been introduced by copolymerization to prepare a 20 mass % MeOH solution. [ka]
[0071] (2) Saponification of denatured EVAc A 10L reaction tank equipped with a jacket, a stirrer, a nitrogen inlet, a reflux condenser, and a solution addition port was charged with 4000 g of a 20% by mass MeOH solution of the modified EVAc obtained in (1) above. The solution was heated to 60°C while blowing nitrogen into it, and a MeOH solution with a 2N concentration of sodium hydroxide was added at a rate of 12 mL / min for 2 hours. After the addition of the sodium hydroxide MeOH solution was completed, the saponification reaction was allowed to proceed by stirring for 2 hours while maintaining the temperature in the system at 60°C. Then, 230 g of acetic acid was added to stop the saponification reaction. Next, 3 L of ion-exchanged water was added while heating and stirring at 80°C, MeOH was discharged outside the reaction tank, and a modified ethylene-vinyl alcohol copolymer (hereinafter referred to as modified EVOH) was precipitated. The precipitated modified EVOH was collected by decantation and pulverized in a mixer. The obtained modified EVOH powder was put into a 1 g / L aqueous acetic acid solution (bath ratio 20: 20 L of aqueous solution per 1 kg of powder) and stirred and washed for 2 hours. The product was deliquinated, and then placed in a 1 g / L aqueous acetic acid solution (bath ratio 20) and washed with stirring for 2 hours. The deliquinated product was placed in ion-exchanged water (bath ratio 20), washed with stirring for 2 hours, and then deliquinated. This operation was repeated three times for purification. The product was then immersed in 10 L of an aqueous solution containing 0.5 g / L acetic acid and 0.1 g / L sodium acetate with stirring for 4 hours, and then deliquinated. The product was then dried at 60°C for 16 hours to obtain 420 g of a crude dried modified EVOH product.
[0072] (3) Manufacturing of modified EVOH hydrous pellets In a 3L stirring tank equipped with a jacket, a stirrer and a reflux condenser, 800g of the crude dried modified EVOH obtained by repeating the above (2) twice, 400g of water and 800g of MeOH were charged and dissolved by heating to 85°C. The solution was extruded through a 4mm diameter glass tube into a mixture of water / MeOH = 90 / 10 cooled to -5°C to precipitate in the form of strands, and the strands were cut into pellets with a strand cutter to obtain hydrous pellets of modified EVOH. The moisture content of the obtained hydrous pellets of modified EVOH was measured with a Mettler halogen moisture meter "HR73" and found to be 55% by mass.
[0073] (4) Production of modified EVOH composition pellets 1650 g of the hydrous pellets of modified EVOH obtained in (3) above were put into an aqueous solution of 1 g / L acetic acid (bath ratio 20) and washed with stirring for 2 hours. The pellets were deliquinated, and then put into an aqueous solution of 1 g / L acetic acid (bath ratio 20) and washed with stirring for 2 hours. After the pellets were deliquinated, the aqueous solution of acetic acid was renewed and the same operation was carried out. The pellets were washed with an aqueous solution of acetic acid, then deliquinated, put into ion-exchanged water (bath ratio 20), washed with stirring for 2 hours, and then deliquinated. This operation was repeated three times to purify the pellets, and hydrous pellets of modified EVOH were obtained from which the catalyst residue from the saponification reaction had been removed. The hydrous pellets were put into an aqueous solution of sodium acetate at a concentration of 0.510 g / L, acetic acid at a concentration of 0.8 g / L, and phosphoric acid at a concentration of 0.008 g / L (bath ratio 20) and immersed for 4 hours with periodic stirring. The pellets were deliquinated and dried at 80°C for 3 hours and at 105°C for 16 hours to obtain modified EVOH composition pellets containing acetic acid, sodium salt, and phosphoric acid compound.
[0074] (5) Content of each structural unit in modified EVAc The ethylene content (a mol % in formula (VII)), the content of structural units derived from vinyl acetate (b mol % in formula (VII)), and the content of structural units derived from MPEDAc (c mol % in formula (V)) in the modified EVAc before saponification were calculated. 1 Calculation was performed using H-NMR. [ka]
[0075] First, a small amount of the MeOH solution of modified EVAc obtained in (1) above was sampled, and the modified EVAc was precipitated in ion-exchanged water. The precipitate was collected and dried at 60°C under vacuum to obtain a dried product of modified EVAc. Next, the dried product of modified EVAc obtained was dissolved in dimethylsulfoxide (DMSO)-d6 containing tetramethylsilane as an internal standard substance, and the solution was analyzed by a 500 MHz spectrometer. 1 Measurements were performed at 80°C using H-NMR (JEOL Ltd.: "GX-500").
[0076] The denatured EVAc obtained in Example 1 1The peaks in the H-NMR spectrum are assigned as follows: 0.6 to 2.2 ppm: methylene proton (4H) of ethylene unit, methylene proton (2H) of vinyl acetate unit, methyl proton (3H) of vinyl acetate unit, methylene proton (2H) of main chain of structural unit derived from MPDEAc, methyl proton (6H) of structural unit derived from MPEDAc unit, methylene proton (4H) of side chain adjacent to quaternary carbon of structural unit derived from MPEDAc 3.7-4.2 ppm: Methylene protons (4H) in the side chain adjacent to the acetoxy group of the structural unit derived from the MPEDAc unit 4.4-5.3 ppm: methine protons (1H) of vinyl acetate units
[0077] According to the above assignment, when the integral value from 0.6 to 2.2 ppm is x, the integral value from 3.7 to 4.2 ppm is y, and the integral value from 4.4 to 5.3 ppm is z, the content of ethylene units (a: mol %), the content of vinyl acetate units (b: mol %), and the content of structural units derived from MPEDAc (c: mol %) are calculated according to the following formulas, respectively. a = (x-3y-5z) / (x-2y-z) × 100 b=4z / (x-2y-z)×100 c=y / (x-2y-z)×100 As a result of calculation using the above method, the content of ethylene units (a) was 32.0 mol%, the content of vinyl ester units (b) was 66.5 mol%, MPEDAc The content (c) of the structural unit derived from the ethylene glycol-based copolymer was 1.5 mol %. The values of a, b, and c in the modified EVAc were the same as the values of a, b, and c in the modified EVOH after saponification treatment.
[0078] (6) Degree of saponification of modified EVOH The 1H-NMR measurement was also performed on the modified EVOH after saponification. The crude dry product of the modified EVOH obtained in (2) above was dissolved in dimethyl sulfoxide (DMSO)-d6 containing tetramethylsilane as an internal standard substance and tetrafluoroacetic acid (TFA) as an additive, and measured at 80°C using a 500MHz 1H-NMR (manufactured by JEOL Ltd.: "GX-500"). Figure 2 shows the 1H-NMR spectrum of the modified EVOH obtained in Example 1. Since the peak intensity at 1.85 to 2.1 ppm is significantly reduced, it is clear that in addition to the ester group contained in vinyl acetate, the ester group contained in the structural unit derived from MPEDAc is also saponified to a hydroxyl group. The saponification degree was calculated from the peak intensity ratio of the methyl proton of the vinyl acetate unit (1.85 to 2.1 ppm) and the methine proton of the vinyl alcohol unit (3.15 to 4.15 ppm). The saponification degree of the modified EVOH was 99.9 mol% or more.
[0079] (7) Melting point of modified EVOH The 3-methylene-1,5-pentanediol obtained in the above (4) (in formula (VI), R 1 , R 2 , R 3 and R 4 A modified EVOH composition pellet (A is a hydrogen atom, A and B are methylene groups, and Y and Z are hydrogen groups) was measured in accordance with JIS K7121 using a differential scanning calorimeter (DSC) "RDC220 / SSC5200H" manufactured by Seiko Denshi Kogyo Co., Ltd., by heating from 30°C to 215°C at a rate of 10°C / min, then quenching to -35°C at 100°C / min, and heating again from -35°C to 195°C at a rate of 10°C / min. Indium and lead were used for temperature calibration. The melting peak temperature (Tpm) was obtained from the chart of the 2nd run according to the JIS, and this was taken as the melting point of the modified EVOH. The melting point was 169°C.
[0080] (8) Sodium salt content and phosphoric acid compound content in modified EVOH composition 0.5 g of the modified EVOH composition pellet obtained in (4) above was placed in a Teflon (registered trademark) pressure vessel, and 5 mL of concentrated nitric acid was added thereto and decomposed at room temperature for 30 minutes. After 30 minutes, the vessel was covered and heated at 150°C for 10 minutes and then at 180°C for 5 minutes using a wet decomposition device (Actac Co., Ltd.: "MWS-2") to decompose the pellet, and then cooled to room temperature. This treatment liquid was transferred to a 50 mL measuring flask (TPX) and made up to 10 mL with pure water. The metal content of this solution was analyzed using an ICP emission spectrometer (PerkinElmer Co., Ltd. "OPTIMA4300DV") to determine the content of sodium and phosphorus elements. The sodium salt content was 150 ppm in terms of sodium element, and the phosphate compound content was 10 ppm in terms of phosphate radical.
[0081] (9) Film preparation Using the modified EVOH composition pellets obtained in (4) above, a single layer film was formed under the following conditions using a 20 mm extruder "D2020" (D (mm) = 20, L / D = 20, compression ratio = 2.0, screw: full flight) manufactured by Toyo Seiki Seisakusho Co., Ltd., to obtain a single layer film of the modified EVOH composition. Cylinder temperature: Feed section 175℃, compression section 215℃, metering section 215℃ Die temperature: 215℃ Screw rotation speed: 40~100rpm Discharge amount: 0.4~1.5kg / hour Take-up roll temperature: 80℃ Take-up roll speed: 0.8~3.2m / min Film thickness: 20μm, 150μm
[0082] In other examples in this specification, the temperature conditions of the extruder were set as follows according to the melting point of the modified EVOH. Cylinder Temperature: Supply section: 175℃ Compression section: Melting point of modified EVOH +30~45℃ Measuring section: Melting point of modified EVOH +30~45℃ Die temperature: Melting point of modified EVOH +30~45℃
[0083] (10) Stretching test The 150 μm thick monolayer film obtained in (9) above was placed in a pantograph-type biaxial stretching device manufactured by Toyo Seiki Seisakusho Co., Ltd., and simultaneously biaxially stretched at stretching ratios of 2×2 to 4×4 at 80° C. The maximum stretching ratio at which the film could be stretched without tearing, unevenness, or local thickness deviation was taken as the maximum stretching ratio. As a result, the film could be stretched without unevenness or local thickness deviation up to a stretching ratio of 4×4. The results are shown in Table 1.
[0084] (11) Oxygen transmission rate measurement The monolayer film having a thickness of 20 μm obtained in (9) above was conditioned at 20° C. and 85% RH for 3 days, and then the oxygen transmission rate was measured under the same conditions (using Mocon's "OX-TORAN MODEL 2 / 21"). The results are shown in Table 1.
[0085] (12) Multilayer film fabrication The modified EVOH composition obtained in (4) above was used as a raw material, and a 3-kind 5-layer co-extruder was used to produce a 5-layer structure of polypropylene layer / adhesive resin layer / modified EVOH layer / adhesive resin layer / polypropylene layer, to produce a multilayer film. Here, maleic anhydride-modified polypropylene was used as the adhesive resin, and the polypropylene layer was 200 μm thick, the adhesive resin layer was 25 μm thick, and the modified EVOH layer was 50 μm thick.
[0086] (13) Peel strength The multilayer structure obtained in (12) above was subjected to the peel strength measurement under the following conditions as an index of interlayer adhesion between the adhesive resin layer and the modified EVOH layer. That is, the multilayer structure obtained was conditioned for 7 days under an atmosphere of 23°C and 50% RH, and then 10 rectangular test pieces of 15 mm x 200 mm were cut out, and the tensile strength at break (gf / 15 mm) was measured using an autograph AGS-H model manufactured by Shimadzu Corporation under the conditions of a chuck interval of 200 mm and a tensile speed of 250 mm / min. Based on the measurement results of the 10 samples, the adhesion was evaluated according to the following criteria. A: All are over 500gf / 15mm B: At least one is less than 500gf / 15mm
[0087] Examples 2 to 6, Comparative Examples 1 to 4 In the above (1), modified EVOH was synthesized and evaluated in the same manner as in Example 1, except that the comonomer, initiator, MeOH, ethylene pressure, VAc conversion rate, and addition rate of the MeOH solution of sodium hydroxide were as shown in Table 2. The results are shown in Table 1.
[0088] Comparative Example 5 (1) Production of modified EVOH composition pellets In Example 1 (1) to (4), 2-methylene-1,3-propanediol diacetate (MPDAc) was used as the comonomer instead of 3-methylene-1,5-pentanediol diacetate, and the initiator, MeOH, ethylene pressure, VAc conversion rate, and addition rate of MeOH solution of sodium hydroxide were as shown in Table 2. The same procedures as in Example 1 (1) to (4) were carried out to produce modified EVOH composition pellets.
[0089] (2) Content of each structural unit in modified EVAc Content of each structural unit in modified EVAc The content of ethylene units (a mol % in formula (VI)), the content of structural units derived from vinyl acetate (b mol % in formula (VI)), and the content of structural units derived from MPDAc (c mol % in formula (VIII)) in modified EVAc were calculated by measuring the modified EVAc before saponification by 1H-NMR.
[0090] [ka]
[0091] First, a small amount of the MeOH solution of modified EVAc was sampled, and modified EVAc was precipitated in ion-exchanged water. The precipitate was collected and dried at 60°C under vacuum to obtain a dried product of modified EVAc. Next, the dried product of modified EVAc was dissolved in dimethylsulfoxide (DMSO)-d6 containing tetramethylsilane as an internal standard substance, and measured at 80°C using a 500MHz 1H-NMR (manufactured by JEOL Ltd.: "GX-500"). Each peak in the 1H-NMR spectrum of modified EVAc is assigned as follows: 0.6-1.0 ppm: methylene protons (4H) of terminal ethylene units 1.0 to 1.85 ppm: methylene protons (4H) of the ethylene unit in the middle part, methylene protons (2H) of the main chain part of the structural unit derived from MPDAc, methylene protons (2H) of the vinyl acetate unit 1.85-2.1 ppm: Methyl protons (6H) of the structural units derived from MPDAc and methyl protons (3H) of the vinyl acetate units 3.7-4.1 ppm: Methylene protons (4H) in the side chain of the structural unit derived from MPDAc 4.4-5.3 ppm: methine protons (1H) of vinyl acetate units
[0092] According to the above assignment, when the integral value from 0.6 to 1.0 ppm is x, the integral value from 1.0 to 1.85 ppm is y, the integral value from 3.7 to 4.1 ppm is z, and the integral value from 4.4 to 5.3 ppm is w, the content of ethylene units (a: mol %), the content of vinyl ester units (b: mol %), and the content of structural units derived from MPDAc (c: mol %) are calculated according to the following formulas, respectively. a=(2x+2y-z-4w) / (2x+2y+z+4w)×100 b = 8w / (2x+2y+z+4w) x 100 c = 2z / (2x+2y+z+4w) × 100
[0093] As a result of calculation by the above method, the content of ethylene units (a) was 32.0 mol%, the content of vinyl ester units (b) was 66.6 mol%, and the content of structural units derived from MPDAc (c) was 1.4 mol%. The values of a, b, and c in the modified EVAc are the same as the values of a, b, and c in the modified EVOH after saponification treatment.
[0094] (3) Degree of saponification of modified EVOH The 1H-NMR measurement was also performed on the modified EVOH after saponification. The crude dry product of the modified EVOH was dissolved in dimethyl sulfoxide (DMSO)-d6 containing tetramethylsilane as an internal standard and tetrafluoroacetic acid (TFA) as an additive, and measured at 80°C using a 500 MHz 1H-NMR (JEOL Ltd.: "GX-500"). Since the peak intensity at 1.85-2.1 ppm in the 1H-NMR spectrum of the modified EVOH was significantly reduced, it is clear that in addition to the ester groups contained in the vinyl acetate, the ester groups contained in the structural units derived from MPDAc were also saponified to hydroxyl groups. The degree of saponification was calculated from the peak intensity ratio of the methyl protons of the vinyl acetate unit (1.85-2.1 ppm) and the methine protons of the vinyl alcohol unit (3.15-4.15 ppm). The degree of saponification of the modified EVOH was 99.9 mol% or more.
[0095] (4) Evaluation of modified EVOH Modified EVOH was synthesized in the same manner as in Examples 1(7) to (13) and evaluated. The results are shown in Table 1.
[0096] [Table 1] [Table 2]
Claims
1. A modified ethylene-vinyl alcohol copolymer having a monomer unit represented by the following formula (I), the contents (mol %) of a, b, and c relative to the total monomer units satisfy the following formulas (1) to (3), and the degree of saponification (DS) defined by the following formula (4) is 90 mol % or more. 【Chemistry 1】 [In formula (I), R 1 , R 2 , R 3 and R 4 represents a hydrogen atom; A and B represent a methylene group; X, Y, and Z each independently represent a hydrogen atom or an acetyl group. 18≦a≦55 (1) 0.01≦c≦20 (2) [100-(a+c)]×0.9≦b≦[100-(a+c)] (3) DS = [(total number of moles of X, Y, and Z that are hydrogen atoms) / (total number of moles of X, Y, and Z)] × 100 (4)
2. A barrier material comprising the modified ethylene-vinyl alcohol copolymer of claim 1.
3. A resin composition comprising the modified ethylene-vinyl alcohol copolymer according to claim 1.
4. 4. The resin composition according to claim 3, comprising the modified ethylene-vinyl alcohol copolymer and an alkali metal salt, the alkali metal salt being contained in an amount of 10 to 500 ppm calculated as the alkali metal element.
5. A molded article having a layer (A) made of the resin composition according to claim 3 or 4.
6. A multilayer structure having at least a layer (A) made of the resin composition according to claim 3 or 4 and a layer (B) containing another thermoplastic resin.
7. 7. The multilayer structure according to claim 6, wherein the layer (A) and the layer (B) are bonded via a layer (C) made of an adhesive resin.
8. 8. The multilayer structure according to claim 7, wherein the adhesive resin is a polyolefin having a carboxyl group, a carboxylic anhydride group, or an epoxy group.
9. The molded article according to claim 5, wherein the areal stretching ratio is 7 times or more.
Citation Information
Patent Citations
JP1972013645U
New ethylene-vinyl alcohol copolymer and ethylene-vinyl alcohol copolymer resin composition comprising the same
JP2006282835A
Modified ethylene-vinyl alcohol copolymer and its manufacturing method
JP2014051647A
(METH)allyl alcohol copolymer and method for producing the same
JP2016047864A
Resin composition, melt-molded article using same, and multilayered structure
WO2017104673A1